(untitled) (CIPEEX, 2022)
THE CEREBROSPINAL FLUID HYPOTENSION CONSISTS OF EXTRAVASATION OF CEREBROSPINAL FLUID CAUSED BY SPONTANEOUS DEFECATION OF THE DURA MATER BY DEHISCENCE OR SPONTANEOUS FOCAL THINNING. THIS STUDY AIMS TO EVALUATE AND REPORT THE COURSE OF A PATIENT WITH SPONTANEOUS CEREBROSPINAL FLUID HYPOTENSION EVIDENCING THEIR ETIOLOGY, CLINICAL STATUS AND TREATMENT. THE REPORT WAS MADE BASED ON A CROSS-SECTIONAL ANALYSIS OF AN UNIDENTIFIED PATIENT, DURING EMERGENCY ROOM CARE. HYPOTENSION HAS BEEN SHOWN TO BE AN UNDERDIAGNOSED PATHOLOGY THAT SHOULD BE CLARIFIED, THUS FACILITATING ITS EARLY DIAGNOSIS AND REDUCTION OF COMPLICATIONS.